Hydrofluoric acid ingestions: Retrospective evaluations from cases reported to the National Poison Data System 2007–2017 - Zachary Illg; Joseph Carpenter; Tim P. Moran; Emily Kiernan; Brian Patrick Murray (Journal of the American College of Emergency Physicians Open)
Abstract Background Hydrofluoric acid (HF) is associated with systemic toxicity, particularly with high‐concentration formulations. However, most existing data describe dermal exposures; there is a paucity of data related to outcomes after ingestions. Objective To determine the morbidity and mortality associated with HF ingestions as reported to the National Poison Data System (NPDS). A secondary objective is to assess for clinical criteria that are associated with serious outcomes after HF ingestion. Methods We performed a retrospective review of HF ingestions reported to the NPDS from 2007 to 2017. Data including patient demographics, exposure and caller sites, electrolyte abnormalities, treatments, and serious (moderate or major effect or death as documented in NPDS) and non‐serious outcomes were abstracted from case narratives. Cases meeting the criteria for a qualifiable HF ingestion were included in the study. Results During the study period, there were 653 HF ingestions reported to NPDS, of which 142 were included in the final data analysis. Most HF exposures occurred in men (68.3%), and the most common exposure site was at the exposed individual's own residence (78.2%). Nearly half of all exposures (46.5%) were due to transfer into a non‐labeled secondary storage container. Total of 45.8% of the cases resulted in a serious outcome. Electrolyte disturbances were associated with an increased risk of a serious outcome. Hypocalcemia was the most frequently reported electrolyte abnormality, occurring in 24.6% of cases. Nine (6.3%) individuals died. Conclusions Mortality after HF ingestion is low. However, a large cohort of exposures occurred after the transfer of HF to secondary containers. Targeted interventions to reduce this practice are necessary to decrease hazardous chemical exposures.